Liberia's run-up to 2017: continuity and change in a long history of electoral politics. Issue 152 (3rd April 2017) - Pailey, Robtel Neajai; Harris, David
SUMMARY: If successfully orchestrated, the October 2017 elections in Liberia will mark the first time in recent memory when a democratically elected Liberian president – Ellen Johnson Sirleaf – will hand over power to a similarly elected head of state. This is very likely to be a close election and our Briefing investigates changes and continuities in the candidates, political parties, electoral processes and the workings of the Liberian state at a watershed moment in a long and shifting democratic history.